An Investigation of the Impact of Social Media on Construction Project Management - Ansam Omar Al-Shehan; Jamal M. Assbeihat (Salehan Institute of Higher Education, 2021)
One of the most important aspects of managing a project is communication. Although this issue has been widely covered in management, a lack of attention has been given in the project management, slight is known as the impact of social media tools on construction project management. The main purpose of the present study is to explore the potential of social media for the construction of the project management and to understand some of the difficulties that arise from social media implementation. For this purpose a 12 question and 20-item questionnaire has been employed and distributed as a soft copy questionnaires among the sample of 400 engineers who work in the construction field, either in the private sector including contracting and consulting companies (grade one and two) or in the public sector in Jordan. The number of participants who said that they apply social media tools in their projects was 357, while 43 participants, were eliminated as they do not apply social media tools in their work. The collected data from 375 participants were analyzed by using the Statistical Package for Social Sciences (SPSS). The results indicated that there is a positive impact of social media on project management and project team in construction projects especially in reducing time. Coringly, the study revealed the existing difficulties that arise from social media use in projects. The study also has concluded that using social media in the project is highly important to organize the management project recently. Doi: 10.28991/cej-2021-03091644 Full Text: PDF